In Vitro Activity of Pentamidine Alone and in Combination with Antibiotics against Multidrug-Resistant Clinical Pseudomonas aeruginosa Strains - Soraya Herrera-Espejo; Tania Cebrero-Cangueiro; Gema Labrador-Herrera; Jerónimo Pachón; María Eugenia Pachón-Ibáñez; Rocío Álvarez-Marín (MDPI AG, 2020)
Multidrug-resistant (MDR) Pseudomonas aeruginosa is a public health problem causing both community and hospital-acquired infections, and thus the development of new therapies for these infections is critical. The objective of this study was to analyze in vitro the activity of pentamidine as adjuvant in combinations to antibiotics against seven clinical P. aeruginosa strains. The Minimum Inhibitory Concentration (MIC) was determined following standard protocols, and the results were interpreted according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints; however, the gentamicin activity was interpreted according to the Clinical and Laboratory Standards Institute (CLSI) recommendations. The bactericidal in vitro activity was studied at 1×MIC concentrations by time-kill curves, and also performed in three selected strains at 1/2×MIC of pentamidine. All studies were performed in triplicate. The pentamidine MIC range was 400-1600 μg/mL. Four of the strains were MDR, and the other three were resistant to two antibiotic families. The combinations of pentamidine at 1×MIC showed synergistic activity against all the tested strains, except for pentamidine plus colistin. Pentamidine plus imipenem and meropenem were the combinations that showed synergistic activity against the most strains. At 1/2×MIC, pentamidine plus antibiotics were synergistic with all three analyzed strains. In summary, pentamidine in combination with antibiotics showed in vitro synergy against multidrug-resistant P. aeruginosa clinical strains, which suggests its possible use as adjuvant to antibiotics for the therapy of infections from MDR P. aeruginosa.